2021
DOI: 10.3390/plants11010083
|View full text |Cite
|
Sign up to set email alerts
|

A VIN3-like Protein OsVIL1 Is Involved in Grain Yield and Biomass in Rice

Abstract: In chromatin remodeling, the post-translational modification of histone proteins is mediated by multimeric protein complexes. VERNALIZATION INSENSITIVE3 (VIN3) forms a complex with Polycomb Repressive Complex 2 (PRC2), which mediates the trimethylation of H3K27 to repress target gene expression. In rice, four genes (OsVIL1-OsVIL4) encoding the VIN3-like proteins are expressed ubiquitously in various tissues. Null mutants of osvil2 display pleiotropic phenotypes such as altered flowering time, floral organ defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Rice Actin1 (OsActin1) was used as an endogenous control to normalize the expression level of the respective genes. All experiments were repeated at least three times, and the relative transcript levels were calculated using the DDCt method (Schmittgen and Livak, 2008;Yoon et al, 2022). The primers used in this study are listed in Supplementary Table 1.…”
Section: Rna Isolation and The Expression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Rice Actin1 (OsActin1) was used as an endogenous control to normalize the expression level of the respective genes. All experiments were repeated at least three times, and the relative transcript levels were calculated using the DDCt method (Schmittgen and Livak, 2008;Yoon et al, 2022). The primers used in this study are listed in Supplementary Table 1.…”
Section: Rna Isolation and The Expression Analysismentioning
confidence: 99%
“…The chromatin immunoprecipitation (ChIP) assay was performed using the protocols described in Haring et al (2007) and Yoon et al (2022) with some modifications. Firstly, the fresh leaves from the OsWRKY7-HA transgenic plants were collected and the proteins and chromatin were cross-linked using 3% formaldehyde.…”
Section: Chromatin Immunoprecipitation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of a new starch biosynthetic gene of maize ( ZmCBM48-1 ), which contains a carbohydrate-binding module 48 (CBM48) domain, altered grain size and thousand grain weight, and increased the starch content in rice [ 16 ]. Yoon et al found that VERNALIZATION INSENSITIVE 3-LIKE 1 (OsVIL1), a homolog of the flowering regulator OsVIL2 in rice, increased grain yield and biomass by directly regulating OsCKX2 expression [ 17 ].…”
Section: Functional Studies Of Genes Regulating Various Traits In Plantsmentioning
confidence: 99%
“…The loss of function of LP leads to an increase in branch number and grain number, which is most likely attributed to up-regulation of CK levels ( Li et al., 2011 ). The chromatin interacting factor VIN3-LIKE1 (OsVIL1) and OsVIL2 directly binds to the promoter of OsCKX2 and regulates H3K27 methylation, resulting in decreased OsCKX2 expression, increased CK levels and an increase in the number of branches and grains ( Yang et al., 2019 ; Yoon et al., 2021 ).…”
Section: Roles Of Phytohormones In Controlling Inflorescence Architec...mentioning
confidence: 99%